Molecular weight of DNA from actinophage MSP2. - Lancaster, W D (1975)
Actinophage MSP2 is infectious for Streptomyces venezuelae S13. Based upon electron microscopy of coliphage T4 mixed with MSP2, MSP2 had a head about 48 +/- 2 nm wide and 87 +/- 5 nm long. DNA from polyoma virus and from coliphages T4 and T7 served as reference markers in estimating the molecular weight of MSP2 DNA from sedimentation in sucrose gradients. Denatured MSP2 DNA was estimated to be about 17 x 10(6) and double-stranded MSP2 DNA was about (36 +/- 1.6) x 10(6) in molecular weight.